(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the logistics processes carried out at cargo terminals in Uzbekistan, in particular the processes of multimodal container transportation. At the same time, a forecasting expression for changes in the flow of multimodal containers transported by road and rail was developed using linear and parabolic equations. The parameters of this forecasting expression were calculated using the least squares method, and the forecast values of container flows for the period 2025-2030 were calculated